2022
DOI: 10.4062/biomolther.2022.004
|View full text |Cite
|
Sign up to set email alerts
|

The Long Search for Pharmacologically Useful Anti-Inflammatory Flavonoids and Their Action Mechanisms: Past, Present, and Future

Abstract: Different types of flavonoids (Fig. 1) from plant origins have been known to possess anti-inflammatory activity in vitro as well as in vivo for decades (For reviews: Kim et al., 1996Kim et al., , 2000. Among these, certain derivatives were reported to possess strong potency at pharmacologically relevant doses. However, some of the reports do not have strong support from researchers including natural product research scientists. To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…As an important contributor to inflammaging in vitro and in vivo , SnC-secreted SASP can cause several age-related diseases by maintaining a proinflammatory internal microenvironment [ 64 ]. Accumulating evidence suggests that attenuating SASP production and age-related inflammation can alleviate age-related diseases and extend healthspan [ 2 , 65 - 67 ]. Our previous study and others have shown that LLIs can delay (or avoid) the onset of major age-related diseases [ 68 - 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an important contributor to inflammaging in vitro and in vivo , SnC-secreted SASP can cause several age-related diseases by maintaining a proinflammatory internal microenvironment [ 64 ]. Accumulating evidence suggests that attenuating SASP production and age-related inflammation can alleviate age-related diseases and extend healthspan [ 2 , 65 - 67 ]. Our previous study and others have shown that LLIs can delay (or avoid) the onset of major age-related diseases [ 68 - 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The broad spectrum of potentially anti-inflammatory activity displayed by biologically active compounds can be tested by way of measuring the inhibition of the cyclooxygenase (COX-1, COX-2) activity [19,20]. These two enzymes take part in the synthesis of several mediators of inflammation, including prostaglandin PGE2, leukotriene B4, and thromboxane A2.…”
Section: Introductionmentioning
confidence: 99%